Dancing muses, roller disco and the phantasmagoric feminine: Reanimating Terpsichore in the movie musical Xanadu (1980). Issue 1 (1st March 2019) - Thomas, Priya A.
This article takes as its main focus Robert Greenwald's cult classic movie musical, Xanadu (1980). Reconsidering Xanadu's distinction as one of the most critically and commercially panned films produced in Hollywood history, my reading uncovers the ways in which the musical's campy, neo-mythological iteration of Terpsichore resuscitates key Romantic leitmotifs of the muse as technosensual, airborne woman. Focusing on the roller skate as wearable technology, I trace Xanadu's muse to its historical predecessors. By extension, I reveal how the moving body's prosthetic territories (i.e. the roller skate and the pointe shoe) and motion media technologies play a central role in reviving Xanadu's muse as the 'phantasmagoric feminine', forming an enduring point of intersection between dance and musical theatre. I develop and theorize this term 'phantasmagoric feminine' within the article in reference to a constellation of representational strategies used in the history of Romantic ballet.